Inventarisasi dan Analisis Hambatan Peningkatan Produktivitas Pinang di Kecamatan Sungai Kakap Kabupaten Kubu Raya Kalimantan Barat - Sulistyowati, Henny; Ruliyansyah, Agus; Pramulya, Muhammad (Perkebunan dan Lahan Tropika, 2026)
Inventory and Analysis of Barriers to Increasing Areca Nut Productivity in Sungai Kakap District, Kubu Raya Regency. Areca nut productivity in Kubu Raya Regency is relatively low, at around 0.86 tons/ha, compared with the national average of 1.53 tons/ha. This indicates that there are still many problems in areca nut farming in Kubu Raya Regency. Based on this, research is needed to inventory and analyze obstacles to increasing areca nut productivity, with the results informing recommendations for policy interventions in Kubu Raya Regency. The research was conducted in Punggur Besar Village, Sungai Kakap District, Kubu Raya Regency, and is a descriptive study using a survey method with respondents as research objects. Primary data were collected using a questionnaire to obtain systematic, objective information on farmer characteristics, technical, economic, and external obstacles experienced in running areca nut farming, while secondary data were obtained from relevant agencies and the literature. The results of the study concluded that areca nut farming in Sungai Kakap District, Kubu Raya Regency is still faced with various obstacles, namely: (1) farmers' limited access to information and technology about good and correct areca nut cultivation, (2) farmers can only sell dried areca nuts to collectors at low prices, (3) farmers do not have access to other sources of financing besides their income, and (4) the role of institutions has not been fully felt by farmers, there has been no special guidance and ongoing technical assistance regarding areca nut farming including its financing.